SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF QUALITY OF LIFE FOR LARGE FAMILIES (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article focuses on the definition of social and psychological characteristics of quality of life for many families in Ukraine. An empirical study of subjective satisfaction with the quality of life of many families in which identified key indicators that need to send a socio-psychological work with this population.
Keywords: quality of life, large family, social and psychological assistance.